Power of Reading: Reading as a Strategy for Learning English - Bharati, Padam Lal (Saptagandaki Journal, 2022)
Why don’t language acquirers take advantage of the power of reading goes the heading of Krashen’s 1997 article in which he cites studies that establish with evidence that through extensive reading learners can acquire larger vocabularies, do better in spelling, writing skills and in tests of grammar. In other words, he claims that reading serves as powerful means of developing one’s competence in the second language because it provides the required input. Drawing from my own experience of exclusively relying on reading strategy for English language learning, I argue, with Krashen, that extensive reading or free voluntary reading is a powerful means of developing the second language competence (Kim & Krashen 1997, Krashen 2004). I adopt autoethnography as my method of inquiry and look back upon my own recollections of how I utilized ‘reading’ as a default strategy in developing a working knowledge of the English language. I use a retrospective composition I wrote back in the year 2012, which recounts my struggle for learning English through my school years to the days of my early career as a teacher of English, as my data text and adopt qualitative interpretive analysis.